Lateralization, functional specialization, and dysfunction of attentional networks. (November 2020) - Mengotti, Paola; Käsbauer, Anne-Sophie; Fink, Gereon R.; Vossel, Simone
Abstract: The present review covers the latest findings on the lateralization of the dorsal and ventral attention systems, their functional specialization, and their clinical relevance for stroke-induced attentional dysfunction. First, the original assumption of a bilateral dorsal system for top-down attention and a right-lateralized ventral system for stimulus-driven attention is critically reviewed. The evidence for the involvement of the left parietal cortex in attentional functions is discussed and findings on putative pathways linking the dorsal and ventral network are presented. In the second part of the review, we focus on the different attentional subsystems and their lateralization, discussing the differences between spatial, feature- and object-based attention, and motor attention. We also review studies based on predictive coding frameworks of attentional functions. Finally, in the third section, we provide an overview of the consequences of specific disruption within the attention networks after stroke. The role of the interhemispheric (im)balance is discussed, and the results of new promising therapeutic approaches employing brain stimulation techniques such as transcranial magnetic stimulation (TMS) or transcranial direct current stimulation (tDCS) are presented.